Advances in Intraoperative Optics: A Brief Review of Current Exoscope Platforms. Issue 1 (13th September 2019) - Langer, David J; White, Timothy G; Schulder, Michael; Boockvar, John A; Labib, Mohamed; Lawton, Michael T
Abstract: BACKGROUND: The advent of the operating microscope (OM) revolutionized the field of neurosurgery. It allowed surgeons to operate on and effectively treat diseases previously inaccessible with conventional eyesight because of magnification and illumination. Improvements in the essential methods of visualization and the quality of the optics have plateaued. Another main limitation of the OM remains its ergonomics because of the need of the surgeon and assistant to directly interface with the OM objective. Recently, exoscopes have been introduced to overcome some shortcomings of the conventional OM. OBJECTIVE: To subjectively review the individual authors experience with the current exoscope platforms in an attempt to provide a resource to the neurosurgeon when considering imaging options. METHODS: Experts with previous use of each individual platform were contacted and asked to contribute their experiences. RESULTS: In total, 4 systems are discussed. They include the VITOM (Karl Storz, Tuttlingen, Germany), the Olympus ORBEYE (Olympus, Tokyo, Japan), the Synaptive Modus V (Synaptive Medical, Toronto, Canada), and the Zeiss KINEVO (Carl Zeiss AG, Oberkochen, Germany). CONCLUSION: The advent of exoscopes has the potential to begin to allow surgeons to move beyond solely the microscope for intraoperative visualization while improving upon its ergonomic disadvantages.